Disability and its correlates among persons with bipolar disorder: Exploratory findings from the bipolar disorder course and outcome study from India (BiD-CoIN study) - Sandeep Grover; Ajit Avasthi; Rahul Chakravarty; Amitava Dan; Kaustav Chakraborty; Rajarshi Neogi; Avinash Desouza; Omkar Nayak; Samir Kumar Praharaj; Vikas Menon; Raman Deep; Manish Bathla; et al. (Indian Journal of Psychiatry)
Aim: This study aimed to evaluate the disability and its correlates in persons with Bipolar Disorder during the remission phase. Materials and Methods: As part of the multicentric study, 773 patients with bipolar disorder, currently in clinical remission, were evaluated for disability on the Indian Disability Assessment Evaluation Scale. Results: About one-fifth of the participants had some level of disability in the domain of self-care, one-third had some level of disability in the interpersonal domain, one-fourth had some level of disability in communication and understanding, and a maximum proportion (43.7%) had some disability in the domain of work. Overall, about one-fifth (18.4%) were considered to have a benchmark disability (i.e., disability >40%). In terms of correlates, those with a disability had a short duration of current remission, a higher number of manic and mixed episodes, a higher mean number of total episodes, spent more time in the episodes, had lower severity of the depressive episodes, higher residual depressive and manic symptoms, had overall higher manic affective morbidity, had a higher level of cognitive deficits, and had poorer insight. Conclusion: A significant proportion of patients with bipolar disorder have disability in work domain, and the presence of residual symptoms of either polarity are associated with higher level of disability.